2014
DOI: 10.1371/journal.pone.0104684
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Expansion of the Pseudogymnoascus destructans Genotype in North America Is Accompanied by Significant Variation in Phenotypic Expression

Abstract: Pseudogymnoascus destructans is the causative agent of an emerging infectious disease that threatens populations of several North American bat species. The fungal disease was first observed in 2006 and has since caused the death of nearly six million bats. The disease, commonly known as white-nose syndrome, is characterized by a cutaneous infection with P. destructans causing erosions and ulcers in the skin of nose, ears and/or wings of bats. Previous studies based on sequences from eight loci have found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…Initial morphological identifications of Pd (using Gargas et al, 2009) were confirmed by sequencing as part of other studies (2012 samples: Khankhet et al, 2014;2015 samples: pers. comm. J.…”
Section: Methodsmentioning
confidence: 71%
“…Initial morphological identifications of Pd (using Gargas et al, 2009) were confirmed by sequencing as part of other studies (2012 samples: Khankhet et al, 2014;2015 samples: pers. comm. J.…”
Section: Methodsmentioning
confidence: 71%
“…Seven of the eight genes sequenced were polymorphic among the European isolates (Tables S1 and S2), sharply contrasting with the absence of variation observed across the North American isolates [4,7]. These data demonstrate the older origin of the European population of P. destructans compared with that of the North American population.…”
mentioning
confidence: 81%
“…Twenty-eight P. destructans isolates, collected from Myotis bats over a five-year timeframe and covering regions in Europe with the highest number of reported cases of P. destructans infection [6] (Figure 1A), were sequenced at eight genomic loci and combined with published data from seventy-one North American isolates covering a similar range and timeframe [4,7] (see Supplemental Experimental Procedures).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some isolates were sent to taxonomic specialists for confirmation of identification, usually through a combination of morphological and molecular genetic techniques. Identifications of Pd were confirmed by sequencing as part of another study (Khankhet et al, 2014). Permanent cultures are housed in the University of Alberta Microfungus Collection and Herbarium (UAMH 11721, 11723-11725, 11732-11734, 11813, 11815-11817) and desiccant-dried samples are vouchered in the New Brunswick Museum 04840,(4942)(4943)(4944)(4945)(4946)(4947)(4948).…”
Section: Laboratory Processingmentioning
confidence: 99%